Challenges and dilemmas of social cohesion between the Rohingya and host communities in Bangladesh - Siddiqi, Bulbul (Frontiers in Human Dynamics, 2022)
Social Cohesion is an important issue for refugees and their host communities. Much attention on social cohesion in the literature has been focused on situations in the Middle East. This paper will bring attention to the Rohingya crisis in Bangladesh. With the influx of nearly one million Rohingya into Bangladesh in 2017, social cohesion between the Rohingya and their host communities has become more complex than ever. Although ensuring social cohesion is very important for Bangladesh, it has not been easy to implement under the present legislative framework of refugee management in Bangladesh. The sympathetic attitude of the host community toward the Rohingya has significantly declined during the past 4 years. In this context, qualitative research was undertaken to understand the challenges and dilemmas of social cohesion from both the host and Rohingya perspectives. Based on 50 key informant interviews, observations, and several informal group discussions, this paper argues that a negative perception among the neighboring host communities toward the Rohingya has increased, contributing to social tension. A pragmatic and sustainable approach has to be taken to ensure a cohesive and peaceful coexistence of the host communities and the Rohingya until dignified repatriation of the Rohingya is possible.